Evaluasi Hasil dan Kandungan Pati Mutan Ubi Kayu Hasil Iradiasi Sinar Gamma Generasi M1V4 - Subekti, Isnani; Khumaida, Nurul; Ardie, Sintho Wahyuning; Syukur, dan Muhamad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Cassava is one of the important starch producer crops. Although Indonesia ranks as the third largest cassava producer country, Indonesia still imports cassava starch to meet the domestic demand in food and non-food industries. Gamma ray irradiation has been implemented to generate cassava mutants in order to support development of superior cassava variety, especially high yield and high starch content, especially high yield and high starch content. The objectives of this research were to evaluate the yield potential and the starch content of gamma irradiated 40 putative cassava mutants at M1V4 generation. This research was arranged in randomized complete block design with three replications and conducted at Cikabayan Experimental Field, IPB, Bogor, from May 2016 to March 2017. The starch content was measured using gravimetric methods. The results showed that five mutants, G2142, G3151, G2141, G1143, and G3111, had higher tuber weight per plant (6-7 kg per plant) compared to the background ‘Gajah’ genotype (4.7 kg per plant). ‘G2112’ mutant genotype showed higher starch content (23.86%) compared to the background ‘Gajah’ genotype (17.65%). The specific gravity (SG) was positively correlated with starch content (r = 0.905), indicated that the higher the SG, the higher the starch content of cassava.Keywords: gravimetric, mutant, specific gravity (SG), yield